2004
DOI: 10.1007/s00438-004-1087-4
|View full text |Cite
|
Sign up to set email alerts
|

Expression of cefD2 and the conversion of isopenicillin N into penicillin N by the two-component epimerase system are rate-limiting steps in cephalosporin biosynthesis

Abstract: The conversion of isopenicillin N into penicillin N in Acremonium chrysogenum is catalyzed by an epimerization system that involves an isopenicillin N-CoA synthethase and isopenicillin N-CoA epimerase, encoded by the genes cefD1 and cefD2. Several transformants containing two to seven additional copies of both genes were obtained. Four of these transformants (TMCD26, TMCD53, TMCD242 and TMCD474) showed two-fold higher IPN epimerase activity than the untransformed A. chrysogenum C10, and produced 80 to 100% mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
2

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 36 publications
1
12
0
2
Order By: Relevance
“…Ullán et al [2004] reported that the reaction in which this enzyme is involved is a limiting step in CPC production in SmF. This limitation was also observed in our SmF versus SSF experiment, where the cefD2 gene showed from 2-to over 10-fold higher expression in SSF than in SmF, concurring with a better intermediate transformation in the CPC biosynthesis pathway during the culture ( fig.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Ullán et al [2004] reported that the reaction in which this enzyme is involved is a limiting step in CPC production in SmF. This limitation was also observed in our SmF versus SSF experiment, where the cefD2 gene showed from 2-to over 10-fold higher expression in SSF than in SmF, concurring with a better intermediate transformation in the CPC biosynthesis pathway during the culture ( fig.…”
Section: Discussionsupporting
confidence: 72%
“…6.4, but these same activities were faster in SSF at a higher pH. Larger amounts of penicillin N were observed only in SmF at the time of maximum CPC production rate, suggesting a better transformation of intermediates in SSF that helps to overcome the limiting step from penicillin N to deacetoxy-CPC, or the previous one from isopenicillin N to penicillin N [Rodríguez- Sáiz et al, 2004;Skatrud and Queener, 1989;Ullán et al, 2004;Zhou et al, 1992].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it was reported that there is a clear correlation between increased IPN-CoA activity and cephalosporin overproduction by amplification of the cefD2 gene in A. chrysogenum. In this study, when the cefD2 gene was amplified in A. chrysogenum, the level of IPN was decreased whereas the level of PN was increased during fermentation compared to the wild-type strain (Ullan et al, 2004). Therefore, it is expected that upregulation of pcbAB and cefD2 by glycerol during exponential phase affects cephalosporin C production by A. chrysogenum M35.…”
Section: Expression Of Pcbab and Cefd2 In A Chrysogenum M35mentioning
confidence: 82%
“…Digested total DNA was separated by agarose gel electrophoresis and blotted onto nylon membranes (Hybond NX, Amersham Pharmacia Biotech) [20]. Southern blot hybridization was performed as previously described [21].…”
Section: Dna Isolation and Southern Blottingmentioning
confidence: 99%